2017
DOI: 10.1096/fj.201700249r
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 4 inhibitor and phosphodiesterase 5 inhibitor combination therapy has antifibrotic and anti‐inflammatory effects in mdx mice with Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is the most common inherited muscular dystrophy. Patients experience DMD in their 20s from cardiac or respiratory failure related to progressive muscle wasting. Currently, the only treatments for the symptoms of DMD are available. Muscle fibrosis, a DMD feature, leads to reduced muscle function and muscle mass, and hampers pharmaceutical therapeutic efficacy. Although antifibrotic agents may be useful, none is currently approved. Phosphodiesterase 4 (PDE4) inhibitors have exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
(69 reference statements)
2
17
0
Order By: Relevance
“…In line with our results, Nio et al [48] reported only a slight mRNA expression of PDE5 in gastrocnemius and, contrary to data obtained in the lung and the heart, oral sildenafil at a single dose of 30 mg/kg did not increase cGMP in such muscle [48]. Thus, a low physiological level of intracellular cGMP and/or a low amount of PDE type 5 in the gastrocnemius muscle might suggest a longer or greater exposure to sildenafil in order to protect skeletal muscle.…”
Section: Discussionsupporting
confidence: 94%
“…In line with our results, Nio et al [48] reported only a slight mRNA expression of PDE5 in gastrocnemius and, contrary to data obtained in the lung and the heart, oral sildenafil at a single dose of 30 mg/kg did not increase cGMP in such muscle [48]. Thus, a low physiological level of intracellular cGMP and/or a low amount of PDE type 5 in the gastrocnemius muscle might suggest a longer or greater exposure to sildenafil in order to protect skeletal muscle.…”
Section: Discussionsupporting
confidence: 94%
“…First, in humans and animal species that can vomit, systemic administration of PDE4 inhibitors is generally associated with a narrow therapeutic window in that similar doses produce both various therapeutic effects (eg, anti‐inflammatory benefits) as well as emesis and nausea. Similarly, we show here that doses as low as 0.04 mg/kg Rolipram (Figure 5B) and 0.2 mg/kg Piclamilast (Figure 5C) induce acute gastric retention in mice, whereas a dose of 1 mg/kg Piclamilast induces gastric retention in the ad libitum model (Figure 3A), which is at or below the doses generally used to produce anti‐inflammatory benefits in these animals 79‐84 …”
Section: Discussionsupporting
confidence: 66%
“…By contrast, compound A significantly suppressed pro‐fibrotic mRNA expression in the kidneys of DOCA‐salt KKA y mice. In a previous study, we also reported that another PDE4 inhibitor, piclamilast, increased plasma cAMP levels along with increased cAMP levels in skeletal muscle 41 . We, therefore, postulated that increased cAMP may contribute to the anti‐fibrotic effects; however, were unable to conclude on its direct ameliorative effect on fibrosis.…”
Section: Discussionmentioning
confidence: 82%
“…In a previous study, we also reported that another PDE4 inhibitor, piclamilast, increased plasma cAMP levels along with increased cAMP levels in skeletal muscle. 41 We, therefore, postulated that increased cAMP may contribute to the anti-fibrotic effects; however, were unable to conclude on its direct ameliorative effect on fibrosis. We then sought to further confirm the anti-fibrotic effect of elevated cAMP levels in vitro using kidney cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation